Social Support and Anxiety in Final-Year Psychology Students’ Career Transition - Salsabila; Cindy Farahdina Fasha; Sarah Amalia; Nurvica Sary; Mukhaira El Akmal (Da'wa Faculty of Islamic State University Salatiga, 2026)
This study aims to explore the relationship between social support and anxiety when facing the job market for students in their 6th to 8th semesters at the Faculty of Psychology, Prima Indonesia University. The method applied in this study is quantitative with a correlational approach, involving 167 students through purposive sampling techniques. The instruments used were social support and anxiety scales that had been tested for validity and reliability. For data analysis, the Pearson Product-Moment technique was used with the help of SPSS version 22 software. The results of the study showed a significant negative correlation between social support and anxiety levels (r = -0,543; p = 0,000), with an effective contribution of 30.5%. This means that the greater the social support received, the lower the level of anxiety experienced in facing the world of work. Conversely, the less social support obtained, the greater the anxiety when facing the world of work for students. This relationship is considered a strong one because social support has been proven to help students overcome anxiety, improve mental health, and support academic success. This study highlights the importance of the role of family, friends, colleagues, lecturers, and a positive and supportive environment.